Magnetic Driving of Relativistic Outflows in Active Galactic Nuclei. I. Interpretation of Parsec-Scale Accelerations - Vlahakis, Nektarios; Königl, Arieh (IOP, 2004)
There is growing evidence that relativistic jets in active galactic nuclei undergo extended (parsec-scale) acceleration. We argue that, contrary to some suggestions in the literature, this acceleration cannot be purely hydrodynamic. Using exact semianalytic solutions of the relativistic MHD equations, we demonstrate that the parsec-scale acceleration to relativistic speeds inferred in sources such as the radio galaxy NGC 6251 and the quasar 3C 345 can be attributed to magnetic driving. Additional observational implications of this model will be explored in future papers in this series.
Keywords: Astrophysics; galaxies: active; Galaxies: Individual: NGC Number: NGC 6251; galaxies: jets; Galaxies: Quasars: Individual: Alphanumeric: 3C 345; ISM: jets and outflows; magnetohydrodynamics: MHD